Estimating the Returns to Education : Accounting for Heterogeneity in Ability - Patrinos, Harry Anthony; Ridao-Cano, Cris; Sakellariou, Chris (World Bank, Washington, DC, 2012)
Typically estimates of the benefits of education investments show average private rates of return for the average individual. The average may not be useful for policy. An examination of the distribution of the returns across individuals is needed. The few studies that have examined these patterns focus on high-income countries, showing investments to be more profitable at the top of the income distribution. The implication is that investments may increase inequality. Extending the analysis to 16 East Asian and Latin American countries the authors observe mixed evidence in middle-income countries and decreasing returns in low-income countries. Such differences between countries could be due to more job mobility in industrial countries, scarcity of skills, or differential exposure to market forces.